2010
DOI: 10.1209/0295-5075/91/62002
|View full text |Cite
|
Sign up to set email alerts
|

The scintillation of liquid argon

Abstract: A spectroscopic study of liquid argon from the vacuum ultraviolet at 110 nm to 1000 nm is presented. Excitation was performed using continuous and pulsed 12 keV electron beams. The emission is dominated by the analogue of the so called 2 nd excimer continuum. Various additional emission features were found. The time structure of the light emission has been measured for a set of well defined wavelength positions. The results help to interpret literature data in the context of liquid rare gas detectors in which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
193
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(207 citation statements)
references
References 25 publications
(36 reference statements)
14
193
0
Order By: Relevance
“…6 in comparison with the emission spectrum observed in [13]. All purification steps described in Sect.…”
Section: Pure Liquid Argonmentioning
confidence: 79%
See 2 more Smart Citations
“…6 in comparison with the emission spectrum observed in [13]. All purification steps described in Sect.…”
Section: Pure Liquid Argonmentioning
confidence: 79%
“…Here we follow this way backwards to emphasize the most critical issues by describing them first. Already in the emission spectra of [13] it was found that it is difficult to remove other rare gases from argon, xenon in particular. Why krypton never played a role in our experiments cannot be answered by the authors, so far.…”
Section: Effect Of Xenon Impuritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,13,14]). Therefore, in the following we will use a nomenclature which is common for the gas phase to describe also the "gas kinetic" processes leading to light emission of LAr, being aware that this terminology might be partly inadequate for the liquid phase.…”
Section: Scintillation Mechanism Of Liquid Argonmentioning
confidence: 99%
“…In addition, they can be cleaned chemically to a high level of purity, which is important in terms of background: radioactive impurities can be removed from the LRg efficiently, as well as even some of the long-lived radioisotopes of other rare gases like 85 Kr from xenon [5]. Also impurities like oxygen or water which alter the light yield [6] or light-emission time constants [6][7][8][9] can be removed.…”
Section: Introductionmentioning
confidence: 99%